ESTUDO DA ESTABILIDADE OXIDATIVA DE ÓLEOS COMESTÍVEIS COMERCIAIS PELO MÉTODO DE RANCIMAT - SOUZA, Eliane Ferreira; RAMOS, Talita Cuenca Pina Moreira; RODRIGUES, Clauber Dalmas; SILVA, Margarete Soares; FIORUCCI, Antonio Rogério (ANAIS DO ENIC, 2017)
-